1998
DOI: 10.1289/ehp.98106217
|View full text |Cite
|
Sign up to set email alerts
|

Hazard screening of chemical releases and environmental equity analysis of populations proximate to toxic release inventory facilities in Oregon.

Abstract: A comprehensive approach using hazard screening, demographic analysis, and a geographic information system (GIS) for mapping is employed to address environmental equity issues in Oregon. A media-specific chronic toxicity index [ and manganese were ranked as the top five chemicals released statewide based on total CI. In contrast, based on total mass, methanol, nickel, ammonia, acetone, and toluene were identified as the top five TRI chemicals released in Oregon. TRI facility rankings were related to the demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…In addition to this work, other researchers have documented similar racial and income disparities among communities hosting TRI facilities [11,12]. Neumann et al discovered that TRI facilities were located disproportionately in people of color neighborhoods and in areas with lower incomes compared to those in the surrounding counties [11]. …”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…In addition to this work, other researchers have documented similar racial and income disparities among communities hosting TRI facilities [11,12]. Neumann et al discovered that TRI facilities were located disproportionately in people of color neighborhoods and in areas with lower incomes compared to those in the surrounding counties [11]. …”
Section: Introductionsupporting
confidence: 52%
“…Additionally, Fricker and Hengarter found a direct relationship between racial composition and presence of TRI facilities [7]. Both Ringquist and Neumann et al found TRI facilities were located in people of color neighborhoods [11,15]. Unlike Ringquist [15], we did not use zip codes but census tracts as the unit of analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous approaches to hazard-ranking environmental contaminants have often been limited by incomplete databases, requiring researchers to base hazard-rankings on “likely present contaminants” rather than on quantified levels of identified contaminants (Baun et al, 2006; Mitchell et al, 2002; Siljeholm, 1997). Another common approach has used toxicity to assess known chemical releases; however, consideration of exposure potential has often been lacking (Dix et al, 2007; Neumann et al, 1998). Finally, other hazard-rankings have focused on acute toxicity, neglecting chronic exposure and its associated health effects (Swanson et al, 1997; USEPA, 1992).…”
Section: Introductionmentioning
confidence: 99%